An Analysis of The Speech Acts Through The Socioculture - Farhan Hasfialdi; Raflis Raflis (Fakultas Sastra Universitas Ekasakti, 2023)
This study entitled Analysis of the Use of Word Speech Action through Socio-Cultural approach : This Speech Action Study aims to analyze speech actions that contain socio-cultural values commonly used in the 'Dictionary of Indonesian Expressions'. The theory used in this study is the theory of Speech Acts by Leech (2017: 39) which focuses on the theory of speech actions. The method used in this study is a qualitative method. The data analysis method uses Primary data and Secondary data by collecting primary data that can be found in the object of study which in this case is from the book 'Dictionary of Indonesian Expressions'. The data collection technique uses sorting techniques and categorizes data from tranksrip or books that are used as research objects into Primary and Secondary data categories and analyzes phrase sentences that contain socio-cultural elements in them. The results of the analysis show the magnitude of the socio-cultural influence on speech action which consists of many factors. Trust and culture are the biggest major factors in being the influence of speech formation and people's attitudes of taking action and speaking.